2012
DOI: 10.1111/1440-1630.12019
|View full text |Cite
|
Sign up to set email alerts
|

Work outcomes and their predictors in the Redesigning Daily Occupations (ReDO) rehabilitation programme for women with stress‐related disorders

Abstract: Return to work seemed possible without a change in the women's perceptions of the worker role; rather they renegotiated their view of the work environment. The Redesigning Daily Occupations programme was found to be promising, with a positive effect on return to work and sick leave reduction. It seemed more suitable for the higher educated and older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
(27 reference statements)
1
28
0
Order By: Relevance
“…• A variety of quasi-experimental designs were used in 12 studies, including prospective studies evaluating a nonrandomized two-group intervention (Karlson 2010;Martin 2013;Netterstrøm & Bech 2010;Nielsen 2002). Other studies used a matched-control (Eklund 2013), partial matched control group (Landstad 2001), or matched comparison (Grossi & Santell 2009;Wästberg 2016;Wåhlin 2012). The quasi-experimental studies included follow-up periods between six months and two years.…”
Section: Study Design and Methods Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…• A variety of quasi-experimental designs were used in 12 studies, including prospective studies evaluating a nonrandomized two-group intervention (Karlson 2010;Martin 2013;Netterstrøm & Bech 2010;Nielsen 2002). Other studies used a matched-control (Eklund 2013), partial matched control group (Landstad 2001), or matched comparison (Grossi & Santell 2009;Wästberg 2016;Wåhlin 2012). The quasi-experimental studies included follow-up periods between six months and two years.…”
Section: Study Design and Methods Usedmentioning
confidence: 99%
“…Facilitating participatory input can be done by using group meetings to address the work tasks and demands in the work group, which has shown to promote individual preparation of RTW with support from the work group. This approach did promote RTW without a change in the workers perceptions of their role in the work group; rather, they renegotiated their view of the work environment to adjust work processes (Eklund 2013).…”
Section: Facilitating Rtw Requires Focused Attention On Work Modificamentioning
confidence: 99%
“…Promising results are reported in two recently published intervention studies: one is a play based intervention to support optimal social development in children with ADHD (Wilkes‐Gillan, Bundy, Cordier & Lincoln, ) and another focuses supporting individuals to reflect on their occupational narratives and develop a vision for their occupational future (Gunnarsson & Björklund, ). Other studies have explored supports for individuals living with mental illness to engage in education and employment; demonstrated positive effects on return to work among women with stress‐related disorders through an intervention focussed on Redesigning Daily Occupations (Eklund, Wästberg & Erlandsson, ); and reported the positive outcomes achieved by adolescents accessing occupational therapy services through the Better Access to Mental Health Initiative in Australia (Kohn, Hitch & Stagnitti, ).…”
mentioning
confidence: 99%
“…This study did not address differences between the ReDO group and the CAU group, but a related study showed that improved perceptions of the work environment were evident in both groups, as indicated by medium effect sizes (0.54 in the ReDO group and 0.75 in the CAU group) from baseline to the 12-month follow-up [61]. The perceptions of the worker role remained largely the same, however, further underlining that perceptions of the work environment might be a feasible avenue when preparing women for return to work.…”
Section: Discussionmentioning
confidence: 87%